92.2k views
2 votes
2) f(x) = 27x^6+ 1524x^3+125

User Chenna
by
4.6k points

1 Answer

4 votes

Answer:

Explanation:

Let x^3 = y

f(x) = 27(x^3)^2 + 1524(x^3) + 125

f(x) = 27 y^2 + 1524y + 125

You can now put this into the quadratic formula. When you do, you get

(y + 0.0821)(y+56.3623) = 0

So now you substitute x^3 into this

(x^3 + 0.0821)(x^3 + 56.3623)

x^3 + 0.0821 = 0

x^3 = - 0.0821

cuberoot x^3 = cube root 0.0821

x = - 0.4346

x^3 = - 56.3623

x = - 3.8341

User Wooseong Kim
by
4.8k points